چاكسازى كارگێڕى لەبوارى ڕاژەى گشتى لە هەرێمى كوردستانى عێراق - Mustapha Rasool Husen; Barzan Ali Rahim (QALAAI ZANIST JOURNAL, 2019)
Our public administrative in Kurdistan Regional Government K.R.G suffer from many problems in system public service, that are related in one way or another to many errors corruption and the absence of honesty from the administrative behavior and consequently these organizations are unable to achieve their goals and outputs This study aims at surrounding the defect phenomenon and diminishing its effects through the honest administration as an active model of the administrative reform in public organizations to New Public Management . The members administrative work and behavioral performance are protected from corruption by adopting the true values that suit the strategic view. this view is the goal that needs to be attained on the level of organizational outputs to serve the public interest